State and Nation: Teleological Aspects of the Political Course of Scotland - Evgenyj Anatolyevich Turin (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article deals with the teleological aspects of the national-state development of modern Scotland. The author expresses the idea that the teleology of the Scottish political course is a kind of antidote to British exclusiveness. Since the relationship between the state and society has always been difficult everywhere, there have always been various forms of statehood in history. Therefore, the author argues, as applied to the realities of British statehood, both unionist and nationalist teleologies mislead the researcher, as well as explanations of the internal and external determinants of the possible disintegration of Britain. It is concluded that the teleology of the political course of Scotland encourages the researcher to analyze the Union from comparative positions. The author believes that a more accurate and comprehensive analysis is needed to track integration and disintegration trends, as well as the revival of national identities over time. In the author’s opinion, such an analysis will allow the Union to be examined at four interrelated levels: functional changes, mass perception, elite strategies and the role of socio-political institutions. None of these levels is decisive, but they all interact and mutually affect each other. Thus, the place and role of Scotland in the evolution of the Union should be studied in a historical context with the involvement of the Scottish statenational experience in all its interpretations.